If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(r + 2) + 5(r + -2) = 200(r + 2)(r + -2) Reorder the terms: 5(2 + r) + 5(r + -2) = 200(r + 2)(r + -2) (2 * 5 + r * 5) + 5(r + -2) = 200(r + 2)(r + -2) (10 + 5r) + 5(r + -2) = 200(r + 2)(r + -2) Reorder the terms: 10 + 5r + 5(-2 + r) = 200(r + 2)(r + -2) 10 + 5r + (-2 * 5 + r * 5) = 200(r + 2)(r + -2) 10 + 5r + (-10 + 5r) = 200(r + 2)(r + -2) Reorder the terms: 10 + -10 + 5r + 5r = 200(r + 2)(r + -2) Combine like terms: 10 + -10 = 0 0 + 5r + 5r = 200(r + 2)(r + -2) 5r + 5r = 200(r + 2)(r + -2) Combine like terms: 5r + 5r = 10r 10r = 200(r + 2)(r + -2) Reorder the terms: 10r = 200(2 + r)(r + -2) Reorder the terms: 10r = 200(2 + r)(-2 + r) Multiply (2 + r) * (-2 + r) 10r = 200(2(-2 + r) + r(-2 + r)) 10r = 200((-2 * 2 + r * 2) + r(-2 + r)) 10r = 200((-4 + 2r) + r(-2 + r)) 10r = 200(-4 + 2r + (-2 * r + r * r)) 10r = 200(-4 + 2r + (-2r + r2)) Combine like terms: 2r + -2r = 0 10r = 200(-4 + 0 + r2) 10r = 200(-4 + r2) 10r = (-4 * 200 + r2 * 200) 10r = (-800 + 200r2) Solving 10r = -800 + 200r2 Solving for variable 'r'. Reorder the terms: 800 + 10r + -200r2 = -800 + 200r2 + 800 + -200r2 Reorder the terms: 800 + 10r + -200r2 = -800 + 800 + 200r2 + -200r2 Combine like terms: -800 + 800 = 0 800 + 10r + -200r2 = 0 + 200r2 + -200r2 800 + 10r + -200r2 = 200r2 + -200r2 Combine like terms: 200r2 + -200r2 = 0 800 + 10r + -200r2 = 0 Factor out the Greatest Common Factor (GCF), '10'. 10(80 + r + -20r2) = 0 Ignore the factor 10.Subproblem 1
Set the factor '(80 + r + -20r2)' equal to zero and attempt to solve: Simplifying 80 + r + -20r2 = 0 Solving 80 + r + -20r2 = 0 Begin completing the square. Divide all terms by -20 the coefficient of the squared term: Divide each side by '-20'. -4 + -0.05r + r2 = 0.0 Move the constant term to the right: Add '4' to each side of the equation. -4 + -0.05r + 4 + r2 = 0.0 + 4 Reorder the terms: -4 + 4 + -0.05r + r2 = 0.0 + 4 Combine like terms: -4 + 4 = 0 0 + -0.05r + r2 = 0.0 + 4 -0.05r + r2 = 0.0 + 4 Combine like terms: 0.0 + 4 = 4 -0.05r + r2 = 4 The r term is r. Take half its coefficient (0.5). Square it (0.25) and add it to both sides. Add '0.25' to each side of the equation. -0.05r + 0.25 + r2 = 4 + 0.25 Reorder the terms: 0.25 + -0.05r + r2 = 4 + 0.25 Combine like terms: 4 + 0.25 = 4.25 0.25 + -0.05r + r2 = 4.25 Factor a perfect square on the left side: (r + 0.5)(r + 0.5) = 4.25 Calculate the square root of the right side: 2.061552813 Break this problem into two subproblems by setting (r + 0.5) equal to 2.061552813 and -2.061552813.Subproblem 1
r + 0.5 = 2.061552813 Simplifying r + 0.5 = 2.061552813 Reorder the terms: 0.5 + r = 2.061552813 Solving 0.5 + r = 2.061552813 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + r = 2.061552813 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + r = 2.061552813 + -0.5 r = 2.061552813 + -0.5 Combine like terms: 2.061552813 + -0.5 = 1.561552813 r = 1.561552813 Simplifying r = 1.561552813Subproblem 2
r + 0.5 = -2.061552813 Simplifying r + 0.5 = -2.061552813 Reorder the terms: 0.5 + r = -2.061552813 Solving 0.5 + r = -2.061552813 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + r = -2.061552813 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + r = -2.061552813 + -0.5 r = -2.061552813 + -0.5 Combine like terms: -2.061552813 + -0.5 = -2.561552813 r = -2.561552813 Simplifying r = -2.561552813Solution
The solution to the problem is based on the solutions from the subproblems. r = {1.561552813, -2.561552813}Solution
r = {1.561552813, -2.561552813}
| 9-3m=-2m | | 14g+7=13g | | c=150+10 | | c=75+10 | | -5(-a-9)=2+6(8+a) | | -7x-3+5x=21 | | 2(m-3)=18 | | 5+15a=100 | | y-16/5=13 | | (x+2)(x+7)=4 | | 12(-3k-5)+9(8-k)=5k+5k+7+3k | | 6:00+41/2= | | x*3=76 | | 6y+20=80 | | 9x^2+36x+20=0 | | 3,5x+8=2(x+7) | | 5a+15a=100 | | 4x^2-15x+10=-4x+4 | | -11n-10n=2(n-3)-2(12+4n) | | 5/8=15/24 | | -11=m+12m | | x^2-x-18=-2x+2 | | 5x+7=7x+27 | | 3/7=6/15 | | 6xsquare-37x=-6 | | 20m-14=10 | | 2(4+3m)=3 | | 2,5(x-2)-1,5x=1 | | 3(k+5)=-8 | | (X-4)=15 | | 6=(1/2)(5)(x) | | 2m+18=6m |